Проблеми аграрної історії України ХІХ – початку ХХ ст. в матеріалах наукових читань на пошану професора Д. П. Пойди - Іваненко, В.В. (Історичний архів. Наукові студії, 2014)
Висвітлено проблеми аграрної історії України ХІХ – початку ХХ ст. у матеріалах
наукових читань, присвячених пам’яті професора Д.П. Пойди. У дев’яти випусках
збірника згруповано у тематичні блоки та проаналізовано за проблемно-хронологічним
принципом понад сто публікацій, які охоплюють ХІХ – початок ХХ ст. Визначено
пріоритетні напрямки досліджень з аграрної історії України, ознайомлено з основними
напрацюваннями науковців. Освещены проблемы аграрной истории Украины ХІХ – начала ХХ в. в материалах
научных чтений, посвященных памяти профессора Д.П. Пойды. В девяти выпусках
сборника сгруппированы по проблемно-хронологическому принципу и проанализированы
более ста публикаций, охватывающие ХІХ – начало ХХ в. Определены приоритетные
направления исследований по аграрной истории Украины, охарактеризованы основные
наработки историков. The problems of agrarian history of Ukraine of 19 – the beginning of the 20th centuries in the
collection of the scientific articles «Questions of agrarian history of Ukraine and Russia»
devoted to Professor D.P. Poyda have been considered. His role in the creation of scientific
school of the study of agrarian history in Dnipropetrovsk University has been shown. In nine
issues of collections more than one hundred publications concerning that history period have
been analyzed. The priority directions of researches of agrarian history of Ukraine and their
territorial scopes have been emphasized; it is concerned with basic investigations and
debatable problems. All publications on problem-chronologic principle are grouped in thematic
blocks: historiography and methodological aspects of agrarian history, position of peasant
economy, mutual relations of peasants and squires, peasant reform of 1861 and its
consequences, agrarian question in public opinion in the 19th century, organization and
functions of peasant self-government authority, the results of its activity for the village,
modernization processes and their influence on the development of peasantry, labour migration
of peasants, distribution of agronomical knowledge among peasants, agrarian question in the
programs of Ukrainian political parties, activity of the peasants in the time of Russian revolution
of 1905-1907, implementing and results of reform by P. Stolypin, mentality, spiritual culture and
way of life of the Ukrainian peasants at the end of 19th – beginning of the 20th centuries. It
allowed us to see all the palette of the materials contained in the collections of publications. On
the basis of the description of historian-agrarian representatives at the scientific readings the allUkrainian
character of collection of articles has been proved.